PENGARUH SINBIOTIK KEFIR PISANG BATU TERHADAP KADAR KOLESTEROL-LDL DAN KOLESTEROL-HDL TIKUS MODEL SINDROM METABOLIK - Dina Khoiriyah; Taufik Maryusman; Santi Herlina (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Effect of Banana Kefir Synbiotic on LDL-Cholesterol and HDL-Cholesterol of Metabolic Syndrome Rats Metabolic syndrome (SM) is characterized by several risk factors including dyslipidemia. This study aims to analyze the effect of kefir synbiotic produced from banana stone flour (Musa balbisiana) on LDL-cholesterol and HDL-cholesterol of metabolic syndrome rat model. The 24 Sprague Dawley rats were divided into four groups, namely negative control (healthy rats fed standard feed), positive control (metabolic syndrome rats fed standard feed), treatment I and treatment II (metabolic syndrome rats each given synbiotic kefir banana stone flour 1.8 mL/200 g mouse BW/day and 3.6 mL/200 g mouse BW/day, respectively). The intervention was carried out for three weeks. After the intervention, the levels of LDL-cholesterol in treatment I and II experienced a decrease of 44.66% and 56.94%, respectively, while the-HDL-cholesterol levels in treatment I and II experienced an increase of 104.5% and 172.71%, respectively. The biggest change occurred in treatment II. Synbiotic kefir banana stone flour improved lipid profile in metabolic syndrome rats. Sindrom metabolik (SM) ditandai dengan beberapa faktor risiko termasuk dislipidemia. Penelitian ini bertujuan untuk menganalisis pengaruh sinbiotik kefir tepung pisang batu (Musa balbisiana) terhadap kadar kolesterol-LDL dan kolesterol-HDL tikus model SM. Subjek menggunakan 24 ekor tikus Sprague Dawley yang dibagi menjadi empat kelompok, yaitu kontrol negatif (tikus sehat yang diberi pakan standar), kontrol positif (tikus model SM yang diberi pakan standar), perlakuan I dan perlakuan II (tikus model SM yang masing-masing diberi sinbiotik kefir tepung pisang batu 1,8 mL/200 g BB tikus/hari dan 3,6 mL/200 g BB tikus/hari). Proses intervensi dilakukan selama tiga minggu. Setelah intervensi, kadar kolesterol-LDL perlakuan I dan II mengalami penurunan sebesar 44,66% dan 56,94%, sedangkan kadar kolesterol-HDL perlakuan I dan II mengalami peningkatan sebesar 104,5% dan 172,71%. Perubahan terbesar terjadi pada perlakuan II. Sinbiotik kefir tepung pisang batu memperbaiki profil lipid tikus sindrom metabolik.